RovM and CsrA Negatively Regulate Urease Expression in Yersinia pseudotuberculosis - Dai, Qingyun; Xu, Lei; Xiao, Lu; Zhu, Kaixiang; Song, Yunhong; Li, Changfu; Zhu, Lingfang; Shen, Xihui; Wang, Yao (Frontiers in Microbiology, 2018)
Urease acts as an important acid resistance system and virulence factor that is widespread among microorganisms. RovM is a global regulator that regulates a series of genes and pathways including acid survival systems in the enteric bacterium Yersinia pseudotuberculosis (Yptb). However, whether RovM regulates the urease activity in Yptb was still unknown. In this study, by using qualitative and quantitative urease assays, we show that the urease expression responds to nutrient conditions and the RovM protein represses urease expression by binding to its promoter. A previously reported positive regulator OmpR activates urease activity but RovM plays a dominant role in different nutrient conditions. In addition, carbon storage regulator system A (CsrA), the upstream regulator of RovM, dramatically down-regulates urease activity possibly by its binding to the Shine-Dalgarno (SD) sequence of the mRNA encoding the urease. In conclusion, this study demonstrates that urease activity is strictly controlled by nutrient conditions and is down-regulated by the CsrA-RovM pathway.